2019
DOI: 10.5194/se-10-117-2019
|View full text |Cite
|
Sign up to set email alerts
|

Anticlockwise metamorphic pressure–temperature paths and nappe stacking in the Reisa Nappe Complex in the Scandinavian Caledonides, northern Norway: evidence for weakening of lower continental crust before and during continental collision

Abstract: Abstract. This study investigates the tectonostratigraphy and metamorphic and tectonic evolution of the Caledonian Reisa Nappe Complex (RNC; from bottom to top: Vaddas, Kåfjord, and Nordmannvik nappes) in northern Troms, Norway. Structural data, phase equilibrium modelling, and U-Pb zircon and titanite geochronology are used to constrain the timing and pressure–temperature (P–T) conditions of deformation and metamorphism during nappe stacking that facilitated crustal thickening during continental collision. Fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…419 Ma are consistent within the errors with the previous whole rock 87 Rb/ 86 Sr ages of Dangla et al (1978). Timing of migmatization event recorded by zircon in the Nordmannvik Nappe i.e., 441 ± 1 Ma and 439 ± 2 Ma (Faber et al 2019) is similar to reported herein. Also, the age constrains on shearing from the Heia locality of 420 ± 4 Ma (Augland et al 2014) support the uniform metamorphic evolution of the Skibotn Nappe Complex.…”
Section: Tectonic Implicationssupporting
confidence: 86%
See 4 more Smart Citations
“…419 Ma are consistent within the errors with the previous whole rock 87 Rb/ 86 Sr ages of Dangla et al (1978). Timing of migmatization event recorded by zircon in the Nordmannvik Nappe i.e., 441 ± 1 Ma and 439 ± 2 Ma (Faber et al 2019) is similar to reported herein. Also, the age constrains on shearing from the Heia locality of 420 ± 4 Ma (Augland et al 2014) support the uniform metamorphic evolution of the Skibotn Nappe Complex.…”
Section: Tectonic Implicationssupporting
confidence: 86%
“…The Vaddas Nappe rocks were metamorphosed mostly under low amphibolite facies conditions, reaching kyanite stability field. In Arnøya, the pressure-temperature (P-T) conditions of metamorphism related to shearing were estimated to 11.7-13.0 kbar at 630-640°C (Faber et al 2019).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations